PERLINDUNGAN HUKUM TERHADAP KORBAN TINDAK PIDANA KEKERASAN DALAM RUMAH TANGGA (KDRT) DI KECAMATAN SINTANG - Kartika Agus Salim (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2021)
At the the case of of domestic violence, the perpetrator usually thinks that he is the highest in the family so that the perpetrator can arbitrarily do whatever he wants, the perpetrator deliberately and consciously in carrying out his actions against the victim.In sociological juridical approach method, law as a social institution that is linked to other social causes. A legal services and protection at Sintang Resort Police are enable the victims to use legal assisstance from advocates. In fact, it is not happen. The investigators coordinate with relevant agencies such as the Social Service and Protection of women and children to assist the victims of doestic violence. This aim to assist the victims at the investigation stage, prosecution, and trial. Furthermore, there are some of limitation faced on this case. The unsupported infrastructure, shelters that have not been well prepared, and the limited of police personnel (policewomen) in providing services to victims ofdomestic violence. Meanwhile, the responsibility for building a shelter is the authority of the Social Service of Sintang Regency, while the police are partners who are members of the P2TPA (Integrated Service Center for the Protection ofWomen and Children) in Sintang Regency.There are some Efforts nust be done through socializing the Law on Domestic Violence to the community. This community especially means the women of neighborhood unit, the Women’s Association, and seminars of family integrity by PPA SATRESKRIM Unit of the Sintang Resort Police. In conclusion, Sintang Police Resort has provided maximum protection to victims of domestic violence. The police officer are providing 1x24 hour service through coordination with the specialists doctors to make sure whether there are minor or serious injuries to the victim and asking social workers to assist when submitting a police report. There is no shelter house yet. The Efforts have been made to protect victims under applicable laws and regulations.